2014
DOI: 10.1179/2047058413y.0000000111
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and conservation of Anne Marie Carl-Nielsen's wax models

Abstract: The Danish sculptor Anne Marie Carl-Nielsen (1863-1945 often prepared three-dimensional models in wax before producing her works of art. The Carl Nielsen Museum in Odense keeps a unique collection of around 200 of the artist's fragile wax models. In 2008 the entire collection was examined, documented, X-ray radiographed, photographed, and conserved. Analyses of five figurines by attenuated total reflectanceFourier transform infrared spectroscopy, optical microscopy, and scanning electron microscopy-energy disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Studies of historical use of modeling material in sculptures have been already reported (Reau, 1930; al., 1987;Mills & White, 1994;Regert et al, 2005Regert et al, , 2006Lattuati-Derieux et al, 2008;Berrie et al, 2010;Gramtorp et al, 2015). Traditionally, clay or waxy natural materials, such as beeswax, were often used for sculpture, especially during the nineteenth century.…”
Section: History Of Mmmsmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies of historical use of modeling material in sculptures have been already reported (Reau, 1930; al., 1987;Mills & White, 1994;Regert et al, 2005Regert et al, , 2006Lattuati-Derieux et al, 2008;Berrie et al, 2010;Gramtorp et al, 2015). Traditionally, clay or waxy natural materials, such as beeswax, were often used for sculpture, especially during the nineteenth century.…”
Section: History Of Mmmsmentioning
confidence: 96%
“…Traditionally, clay or waxy natural materials, such as beeswax, were often used for sculpture, especially during the nineteenth century. Some additives, such as minerals, starch, or pine resin, could also be mixed with these waxy materials in order to change the physical properties or aspect (Colinart et al, 1987;Regert et al, 2005;Berrie et al, 2010;Gramtorp et al, 2015). At this time, however, some alternative synthetic materials introduced new formulations for modeling materials.…”
Section: History Of Mmmsmentioning
confidence: 97%
“…Recently, this degradation phenomenon was observed in a beeswax model, in which metal soaps were produced by reaction between the copper containing metal (used as inner structure of wax model) and free fatty acids in the wax or fatty acids originating from hydrolysis of the wax esters (Gramtorp et al, 2015).…”
Section: Raman and Ftirmentioning
confidence: 99%
“…stearin or glyceryl tristearate, beeswax) incorporated into mineral wax, a common formulation of wax mixture recipes in the 19th century Table 2. Marker peaks were labelled [25]. It might also be possible that commercial oil paint containing zinc stearate additive was used [20], which if true, would imply that brass paint for the brown outlines was applied at a later date after 1918.…”
Section: Characterisation Of Brown Outlinesmentioning
confidence: 99%